Supportive (Maintenance) Therapy in Hematopoietic Stem Cell Transplantation: Main Principles and New Perspectives - VP Pop; OA Rukavitsyn (Клиническая онкогематология)
Supportive (maintenance) therapy (ST) for hematopoietic stem cell transplantation (HSCT) is undergoing significant changes and development. The aim of the review was to summarise the basic data on methods and perspective of ST for HSCT and to analyse new opportunities and alternative approaches to enhance the antitumor potential of HSCT. The need for ST is constantly growing as a result of significant increase in the number of performed HSCT and an increase in patient survival. The review highlights traditional methods of ST which allowed to boost the success of HSCT: antibacterial, antifungal, and antiviral preventive treatment. The authors discuss preventing toxicity of dimethyl sulfoxide (cryopreserving agent); understudied aspects of vaccination of HSCT recipients, and effects on microbiota. The study demonstrates that many of the classic recommendations of ST are being constantly updated given the wide variability of approaches not only to post-transplant monitoring, but also to empirical antibiotic therapy and the use of hematopoietic growth factors and the appropriateness of the correction of the microbiota, constraints of the external environment and social contacts. Currently, HSCT is becoming more available, in conditions close to the out-patient clinics, which leads to improved outcomes and significantly decreases the cost of hospital stay. The future improvement of the cost effectiveness and quality of ST will be possible due to health information technologies, and digital infrastructure between doctor and patient. We report our own experience of ST for allo-HSCT in 19 patients and for auto-HSCT in 82 patients, and implementation of auto-HSCT in non-insulated wards without HEPA-filtration. The literature review shows both the increased demand for the various methods of ST at HSCT and its increasing efficiency. Despite the lack of uniform standards, introduction of new approaches of ST should significantly improve HSCT outcomes.